Konflik Lahan Bandara Melalan Di Kampung Gemuhan Asa Kabupaten Kutai Barat: Land Conflict of Melalan Airport in Gemuhan Asa Village, Kutai Barat District - Yosua Rumopa (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2020)
This research aims at finding the root causes and conflict resolution process between local community of Gemuruh Asa Village and the Kutai Barat Indonesian Air Force Base (TNI AU) on the land ownership issue of Melalan Airport, claimed by both parties. This study uses qualitative research methods with data collection techniques of bibliographical study, field observation, interviews and documentary research. Findings show that the conflicts between the community and the Indonesian Air Force occurred due to differing land ownership claims, where the community claims that their land is inherited from their ancestors while the Indonesian Air Force says the land belongs to state and, as a state organ, the Air Force must protect this state asset. Administratively, the people of Gemuhan Asa village do not have land ownership certificates, but customary rights are not solely related to “paper as proof”. The use of rigid claims based on formal law and customary law by respective parties would not solve the conflict, while the use of some alternative conflict resolution approach in the form of negotiation and mediation needs commitment, effort, trust, and time. Keywords: TNI AU, local community, conflict, Melalan Airport, Kutai Barat